WAAC-4 Series of Medical Examination as an Initial Phase of Rehabilitation Program in Lutung Jawa Conservation - Nurina Titisari; Ahmad Fauzi; Aldila Noviatri; Dian Vidiastuti; Ida Masnur; Iwan Kurniawan (Hemera Zoa, 2018)
Javan Langur Center (JLC) is a rehabilitation center that located in coban talun, Batu, East Java. It is a part of the Javan Primate Project.  The main activity is treating, training behavioral and also habituation and forest classes (soft release) by placing the animal in habituation cage at certain period of time (1). The habituation cage consists of 3 cages namely treatment, quarantine and socialization. But before sending the animal to the cage, it must be free of disease before grouped with other Lutung Jawa. For this reason, a series of medical examination process is conducted. Healthy animals will be sent to habituation cages for intensive training and adaptation in the forest. While the sick animals will undergo the process of therapy and treatment at the treatment cage. This medical examination is an important initial step to determine the next rehabilitation action so it is necessary to perform the procedure appropriately.The purpose of this study was understanding the series of medical examination activities conducted at the JLC rehabilitation center and also aware of the Lutung Jawa physiology status in the time medical examination was held.